Rethinking gastroesophageal reflux disorder. Issue 1 (1st September 2020) - Banting, Samuel P.; Badgery, Henry E.; Read, Matthew; Mashimo, Hiroshi
Abstract: Gastroesophageal reflux disease (GERD) is a common clinical condition for which our understanding has evolved over the past decades. It is now considered a cluster of phenotypes with numerous anatomical and physiological abnormalities contributing to its pathophysiology. As such, it is important to first understand the underlying mechanism of the disease process for each patient before embarking on therapeutic interventions. The aim of our paper is to highlight the mechanisms contributing to GERD and review investigations and interpretation of these results. Finally, the paper reviews the available treatment modalities for this condition, ranging from medical intervention, endoscopic options through to surgery and its various techniques.